Diagnostic performance of rapid antigen testing for SARS-CoV-2: the COVid-19 AntiGen (COVAG) extension study - Wertenauer, Christoph; Dressel, Alexander; Wieland, Eberhard; Wertenauer, Hans-Jörg; Braitmaier, Helmine; Straub, Anna; Helfert, Stefan; Lützner, Nicolas; März, Winfried (Frontiers in Medicine, 2024)
Background: This study is the extension of the COVAG study. We compared two RATs, the Panbio COVID-19 Ag Rapid Test (Abbott) and the SD Biosensor Q SARS-CoV-2 Rapid Antigen Test (Roche), against RT-PCR on the foil of new variants. Methods: We included 888 all-comers at a diagnostic center between October 20, 2021, and March 18, 2022. RT-PCR-positive samples with a Ct value ≤ 32 were examined for SARS-CoV-2 variants. Findings: The sensitivity of the Abbott-RAT and Roche-RAT were 65% and 67%, respectively. For both RATs, lower Ct values were significantly correlated with higher sensitivity. For samples with Ct values ≤ 25, the sensitivities of the Roche-RAT and of the Abbott-RAT were 96% and 95%, for Ct values 25-30 both were 19%, and for Ct values ≥ 30 they were 6% and 2%, respectively. The RATs had substantially higher sensitivities in symptomatic than asymptomatic participants (76, 77%, vs. 29, 31%, for Abbott-RAT, Roche-RAT, respectively) and in participants referred to testing by their primary care physician (84%, 85%) compared to participants who sought testing due to referral by the health department (55%, 58%) or a warning by the Corona-Warn-App (49%, 49%). In persons with self-reported previous Covid-19 sensitivities were markedly lower than in patients without previous Covid-19: 27% vs. 75% for Roche-RAT and 27% vs. 73% for Abbott-RAT. We did not find significant correlation between vaccination status and sensitivity. The Omicron variant was detected with a sensitivity of 94% and 92%, the delta variant with a sensitivity of 80% and 80% for Abbott-RAT and Roche-RAT, respectively. This difference is attributable to the lower Ct values of the Omicron samples compared to the Delta samples. When adjusted for the Ct value, a multivariate logistic regression did not show a significant difference between Omicron and Delta. In terms of sensitivity, we found no significant difference between the wild-type and the Omicron and Delta variants, but a significantly lower sensitivity to the alpha variant compared to the other variants. The specificities were >99% overall.